Panel, composition for forming coating and method for manufacturing panel
By applying a partial crosslinked polymer coating on the bottom of the core layer of the extruded elastic floor or wall panel, the migration of plasticizer is prevented, and the adhesive liquefaction and panel warping caused by plasticizer migration is solved, and the stability is achieved adhesion and paneling performance.
Patent Information
- Application Number
- CN202311871000.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2023-12-29
- Publication Date
- 2025-01-14
AI Technical Summary
With the high mineral filler content, plasticizer migration causes adhesive liquefaction and panel warping, affecting the bonding effect and safety, and difficult to maintain long-term bonding.
A polymer coating with at least partially crosslinked is located on the bottom of the core layer to prevent plasticizer from migration and to form a mechanical barrier through the crosslinking density and void structure to prevent plasticizer from migration through the coating while maintaining shrinkage of the coating rate and rigidity.
Effectively prevent plasticizer from migration, maintain the stability of the adhesive and the flatness of the panels, improve the adhesion between the panels and the substrate, extend the adhesion, and ensure the wear resistance and flexibility of the panels.
Smart Images

Figure CN119308491A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a panel. The present invention also relates to a composition for forming a coating and a method for producing a panel. Background Art
[0002] Extruded resilient floor or wall panels typically include a core material containing a binder such as a thermoplastic elastomer or a flexible polymer. These binders are typically thermoplastic polymers that have desirable properties such as moisture resistance, heat resistance, and impact resistance. Common binders are polyvinyl chloride (PVC) and polypropylene (PP) or other thermoplastic polymers because they are easy to process in extrusion, calendaring, and heat lamination processes.
[0003] In addition to the adhesive, extruded resilient floor or wall panels usually also include inorganic mineral fillers. These inorganic mineral fillers are usually added to the core material of the extruded resilient floor or wall panel, and can bring benefits such as increased thermal stability, enhanced rigidity and toughness, and improved elastic modulus and hardness. By adding certain inorganic mineral fillers to the core material, flame retardant and smoke retardant properties can also be imparted. However, the addition of inorganic mineral fillers to the core material can only produce benefits to a certain extent, an upper limit or below the saturation point. The so-called saturation point refers to the point where the weight ratio between the adhesive and the inorganic mineral filler is further increased and the performance of the board is negatively affected. Beyond this point, the difference in interfacial compatibility and adhesion between the inorganic mineral filler and the adhesive (usually a thermoplastic polymer) and the agglomeration of the inorganic mineral filler will lead to a decrease in the tensile strength, impact strength and compressive strength of the floor or wall panel. In addition, it is observed that the processing performance of the composition extruded to form the resilient floor will drop sharply. Since the inorganic mineral filler is relatively cheap, increasing the content of the inorganic mineral filler in the core material reduces the product cost and can bring the above benefits. The weight ratio of mineral filler to thermoplastic binder is preferably at least 2.5: 1, and the weight ratio of mineral filler to binder may be even higher, such as 3: 1, or even up to a saturation point of 3.5: 1. The saturation point depends on the type and properties of the inorganic mineral filler and the type of binder and may therefore differ from 3.5: 1.
[0004] In order to further increase the weight ratio of inorganic mineral filler to binder to exceed this saturation point, it is known to add a large amount of plasticizer to the mixture of inorganic mineral filler and binder to improve the plasticity of the core material during extrusion and to improve its elasticity and durability in use. The use of plasticizers can further increase the weight ratio of inorganic mineral filler to binder to 4:1, or even to 4.5:1. Other additives, such as waxes, lubricants and coupling agents, can also be used to improve the processing properties of these high mineral content polymer compositions.
[0005] Generally, the plasticizer content is in the range of 2-3% of the total weight of the panel. The addition of plasticizers is even more important when producing flexible, resilient flooring for adhesive installation, commonly known as luxury vinyl tile (LVT), by an extrusion process. The flexibility and deflection of LVT panels can be tested according to ISO 24344 or ASTM F137. When tested according to ISO 24344 or ASTM F137, LVT needs to be flexible enough to bend 180° around a mandrel with a diameter of 25 / 38 mm. In order to extrude flexible LVT with a relatively high mineral content, i.e. a weight ratio of mineral filler to thermoplastic binder of at least 3.5:1, the plasticizer content should be increased with increasing mineral content to at least 4% of the total weight of the panel, and may even be increased to 6% or 8% of the total weight of the panel.
[0006] However, combining a binder (eg, a thermoplastic elastomer or a flexible polymer binder such as PVC or PP), an inorganic mineral filler in a weight ratio to the binder exceeding 3.5:1, and at least one plasticizer presents a number of technical challenges.
[0007] The first challenge is that the surface energy of the panel core material is relatively low, 24-32 dyn / cm, when the core material includes thermoplastic elastomers and / or flexible polymers. Surface energy in this range, measured according to ASTM D7490-13, is insufficient for proper wetting, application and bonding of the adhesive. One solution to this is to corona or plasma treat the back of the core material before applying the adhesive, which can achieve a limited increase in surface energy, at least for a certain time. However, since this increase in surface energy is limited in time, it is not a suitable solution for panels that are installed by glue, as the adhesive is applied when the panel is installed, which may be weeks or months after production. Flexible panels with low surface energy are also expected to cause adhesion and adhesive compatibility issues, which are a major factor or root cause of installation failures and quality complaints.
[0008] Plasticizers are low molecular weight processing aids that improve processing properties. As mentioned above, increasing the mineral content of the panel core material usually requires a corresponding increase in the plasticizer content of the panel core material. Plasticizers can be divided into internal plasticizers and external plasticizers. External plasticizers do not react with the polymer. External plasticizers are different from internal plasticizers, which react with the polymer chains and form part of the polymer chains. External plasticizers act by reducing the cohesion between polymer chains and do not bind to the polymer chains, but are only attracted to the polymer chains through van der Waals forces, i.e. weak intermolecular cohesive forces that arise between molecules due to temporary fluctuations in electron density. Plasticizers can weaken these cohesive forces by disrupting the intermolecular interactions between the chains, thereby making the polymer matrix more flexible and less brittle.
[0009] Plasticizer migration can occur when weak intermolecular forces between the plasticizer and polymer chains are overcome by other forces, or due to differences in concentration between the plasticizer in the polymer matrix and the surrounding or adjacent materials. Heat can increase the rate of this migration by increasing the kinetic energy of the molecules, thereby allowing them to move faster and more easily overcome van der Waals forces. In addition, heating can also simultaneously increase the permeability of the polymer matrix, making it easier for the plasticizer to migrate out of the material. Therefore, the plasticized extruded core material present in a standard non-homogeneous resilient floor or wall panel will exhibit varying degrees of plasticizer migration.
[0010] The second challenge is the liquefaction of the adhesive layer due to the adhesive’s attraction to the plasticizer. This attraction is due to the adhesive’s strong polar or ionic properties, which attract and interact with polar or ionic functional groups on the plasticizer molecules. As the adhesive between the panel layers liquefies, the adhesion between the layers is lost and the layers begin to separate or delaminate. Therefore, plasticizer migration can directly affect the composition of the adhesive layer, resulting in quality issues. In the case of resilient decking directly adhered to the substrate by adhesive, this can mean catastrophic delamination. In the case of resilient wallboard adhered to a vertical substrate, this delamination can even cause safety issues. Even in the case of pre-bonded or separately installed underlayment beneath the flooring, plasticizer migration can cause the polymeric structure of the underlayment to be disrupted, causing it to become brittle and even crack or disintegrate. The market is demanding more sustainable plasticizers, moving away from harmful but highly compatible phthalate plasticizers to less compatible terephthalate plasticizers and even bio-based plasticizers. Therefore, plasticizer migration in the paneling represents a quality issue and additional safety risk that needs to be addressed.
[0011] The third challenge is that applying a curable coating to the panels can cause the panels to warp, especially on panels with a higher plasticizer content. As the coating shrinks during the curing process, the panels are pulled together, resulting in uneven panels. When this warped panel is subsequently installed on a floor or wall, additional adhesive is required to compensate for the bowing of the panel and can result in gaps and height differences between panels. As a result, the final bond of the panel to the floor or wall is not ideal. Summary of the invention
[0012] It is therefore an object of the present invention to provide a panel suitable for permanent and secure adhesion to a floor or wall.
[0013] In a first aspect, the present invention provides a panel, in particular a floor panel, a wall panel or a building panel, comprising: at least one core layer, the core layer comprising at least one mineral filler, at least one polymer binder, and optionally at least one plasticizer; and at least one coating located on the bottom surface of at least one core layer; wherein at least one coating preferably comprises an at least partially cross-linked polymer, which is preferably impermeable to the plasticizer.
[0014] At least one coating on the underside of the core provides a barrier on the underside of the core to prevent migration of plasticizers through the coating. Thus, when the panel is bonded to a substrate or surface with an adhesive, the bond is maintained longer because the adhesive does not liquefy under the influence of the plasticizer. Minerals are compounds classified as minerals by the International Mineralogical Association (International Mineralogical Association New Mineral List, Updated May 2023). Thus, a mineral filler is a mineral used to fill another compound or material.
[0015] A plasticizer is a compound added to a material to soften it and increase its flexibility. Plasticizers can increase the plasticity of a material and reduce viscosity. Depending on the size of the plasticizer, the cross-linked polymer in the coating should preferably have a certain cross-link density to prevent the plasticizer from migrating through the coating. The cross-link density is defined as the number of effective cross-links per unit volume or unit weight, which is inversely proportional to the molecular weight (Mc) between the cross-link points.
[0016] Preferably, the at least partially cross-linked polymer comprises a cross-linked polymer network.A cross-linked polymer network comprises polymer chains linked together by covalent bonds and thus forming a network.
[0017] According to the present invention, the coating comprises a polymer that is at least partially crosslinked. The coating is applied on at least a portion of the bottom surface of the core layer. Prevent at least one plasticizer from migrating through the coating from the core layer by the polymer that is at least partially crosslinked, the polymer comprising a network of crosslinks and voids, the crosslinks and voids being defined by crosslink density and corresponding average void size. According to the present invention, the crosslink density XLD of the polymer that is at least partially crosslinked in the coating is converted into a crosslinked polymer matrix to form a plurality of voids, and the voids have an average void diameter (Vdia).
[0018] A high crosslink density results in a relatively small average void diameter, a high bulk density, a hard cured composition, and a high shrinkage. A low crosslink density results in a relatively small average void diameter, a low bulk density, a flexible cured composition, and a low shrinkage. The crosslink density can be expressed as a percentage between 0% (no crosslinking) and 100% (complete crosslinking).
[0019] The cross-linked polymer is preferably formed by polymerizing and cross-linking at least one oligomer and at least one monomer with a photoinitiator. Preferably, at least one monomer is an acrylic monomer. Assuming a typical molecular weight of about 100 g / mol for acrylic monomer units, the density of the cross-linked polymer is estimated to be about 1.2 g / cm 3 The range of void diameters when the crosslinking density is 40%, 50%, 60% and 70% is:
[0020] 40% cross-link density: 50-80nm
[0021] 50% cross-link density: 40-60nm
[0022] 60% cross-link density: 30-50nm
[0023] 70% cross-link density: 0.1-0.4nm.
[0024] Through experiments and theory, it was found that 60%-70% crosslink density is the threshold crosslink density, above which the average void diameter decreases exponentially. By controllably reducing the average void diameter of the crosslinked polymer in the coating, an inert mechanical barrier can be formed through which plasticizer molecules cannot migrate without affecting the shrinkage and rigidity or brittleness of the crosslinked polymer and the coating.
[0025] According to the above, the at least partially cross-linked polymer may have a cross-link density (XLD) of at least 50%, more preferably at least 60%, and most preferably at least 65%. In particular, the XLD may be in the range of 60% to 75%, such as 65% to 70%. Thus, the cross-linked polymer will exhibit an optimal plasticizer sealing effect, which can be measured by the migration rate of the plasticizer from the core layer through the at least one cross-linked polymer coating. When measured according to ISO 177:2016, the migration rate is less than 0.1 mg / cm 2 , more preferably less than 0.01 mg / cm 2 The average diameter of the voids within such a cross-linked polymer or cross-linked polymer network is preferably less than 3 nm, more preferably less than 1.5 nm, and most preferably less than 1 nm. Specifically, the average void diameter within the cross-linked polymer matrix is most preferably less than the average diameter of at least one plasticizer. Thus, the function of the cross-linked polymer and / or coating as a barrier layer or sealing layer is enhanced, mechanically / physically hindering the diffusion / migration of the plasticizer to other layers.
[0026] Another way to quantify the amount of crosslinking in a polymer network is to quantify the number of double bonds remaining per unit molecular weight. For example, difunctional methacrylates are able to polymerize and form crosslinked three-dimensional polymer structures. The crosslinking of these structures can be determined by quantifying the double bonds remaining after crosslinking, or the crosslink density (XLD). Typically, in 1000 g / mol of polymer, about 5-10 double bonds remain after crosslinking. Generally speaking, this equates to about 50-70% of the double bonds being available for crosslinking. The number of double bonds available for crosslinking depends on the polymer itself.
[0027] Preferably, the crosslinking density of the crosslinked polymer is in the range of 0.01-0.1 mol / g, preferably in the range of 0.02-0.05 mol / g, more preferably in the range of 0.025-0.035 mol / g, most preferably in the range of 0.028-0.032 mol / g, especially measured according to ASTM D2765-16. 3 The crosslink density can be expressed in terms of moles per unit weight or moles per unit volume. If the crosslinked polymer in the plasticizer seal or coating is an acrylate polymer, its molecular weight is typically in the range of 10,000-50,000 g / mol.
[0028] Preferably, the cross-linked polymer network includes a plurality of voids, and the average void diameter is preferably less than or equal to twice the radius of gyration (Rg) of the plasticizer or the diameter of gyration. This can effectively block the migration of the cross-linked polymer network to the plasticizer without becoming brittle or lacking elasticity. The diameter of gyration of a molecule such as a plasticizer is determined by the atomic distribution around its center of gravity. The diameter of gyration is given by the root mean square distance of the molecular chain segments from its center of mass. For polymers, it can be used to measure the size of a molecule. This diameter of gyration of a molecule depends on factors such as molecular weight, molecular structure (such as whether there are side chains or crosslinking) and whether the molecule is swollen by solvents.
[0029] Plasticizers can have linear or cyclic structures, but their molecular weight is usually limited to the range of 100-3000 g / mol, and their diameter (i.e., twice their radius of gyration) is usually between 0.3-10 nm. Examples of some plasticizers and their molecular weight (range) and void diameter (expressed as twice the radius of gyration) are given in Table 1.
[0030] Table 1: Plasticizer weights and diameters.
[0031]
[0032]
[0033] Preferably, the plasticizer migration rate through the coating, especially the plasticizer migration rate of the plasticizer measured according to ISO 177:2016, is less than 0.01 mg / cm2 , more preferably less than 0.005 mg / cm 2 , most preferably less than 0.001 mg / cm 2 . Thus, the coating is substantially impermeable to the plasticizer.
[0034] In one embodiment, the weight ratio of mineral filler to polymer binder is at least 3.5:1, preferably at least 4.0:1, and most preferably at least 4.5:1. A relatively high content of mineral filler has a positive effect on the wear resistance of the panel. However, mineral fillers are relatively brittle. In order to make the panel sufficiently flexible, a relatively high content of plasticizer is required. Therefore, based on the total weight of the core layer, the weight percentage of plasticizer is at least 4 weight%, preferably at least 6 weight%, and more preferably at least 8 weight%. The coating located on the bottom surface of the core layer can prevent the plasticizer from migrating out of the core layer. In particular, when the panel is adhered to a surface (such as a floor) by an adhesive layer, the plasticizer in the core layer tends to migrate to the adhesive layer. The coating prevents this migration.
[0035] The binder may comprise a thermoplastic elastomer, a polymer having a glass transition temperature below 0°C measured according to ISO 6721-11:2019, a biopolymer, a synthetic resin or any combination thereof. A thermoplastic is a polymer that softens and becomes pliable when heated and solidifies when cooled. The heating and cooling process of a thermoplastic and the associated transition from a pliable form to a firm form can be repeated almost infinitely. An elastomer is a material comprising polymer chains that enable the elastomer to recover its shape after deformation. The thermoplastic elastomer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polyvinyl chloride (PVC), chlorinated polyvinyl chloride (CPVC), chlorinated polyethylene (CPE) or any combination thereof. The thermoplastic elastomer and the mineral filler should preferably be mixable to form a homogeneous melt before extrusion. The plasticizer is preferably evenly distributed throughout this melt.
[0036] It is contemplated that the at least partially cross-linked polymer may contain at least one carboxyl functional group and / or at least one amine functional group that can react with the plasticizer. These functional groups may react with the plasticizer to form covalent bonds, thereby reducing the mobility of the plasticizer. This is particularly advantageous when the diameter of the voids of the cross-linked polymer varies and the diameter of at least some of the voids (expressed as twice the radius of gyration of the plasticizer) exceeds the average diameter of the plasticizer. The ability of the at least partially cross-linked polymer to react with the plasticizer is a fail-safe mechanism that ensures that the coating prevents diffusion and migration of the plasticizer through the coating to other layers (such as the adhesive layer).
[0037] In contrast to the above, the cross-linked polymer may be inert to the at least one plasticizer. Advantageously, the cross-linked polymer does not react with the at least one plasticizer, so that the structure of the cross-linked polymer is maintained and the plasticizer molecules are not extracted from the core layer. When the plasticizer molecules remain in the core layer, the panel retains its flexibility. This is particularly advantageous when the variation in the void diameter is relatively small, for example when the void diameter is between the gyration radius of the plasticizer and three times the gyration radius of the plasticizer. Therefore, the plasticizer may be an external plasticizer.
[0038] The plasticizer may be selected from diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), diethylhexyl phthalate (DEHP), dibutyl phthalate (DBP), butyl benzyl phthalate (BBP), di(2-ethylhexyl) adipate (DEHA), di(2-ethylhexyl) sebacate (DOS), di(2-ethylhexyl) terephthalate (DOTP), diisononyl cyclohexane-1,2-dicarboxylate (DINCH), triethyl citrate (TEC), di(2-ethylhexyl) phthalate (DEHP), di-n-octyl phthalate (DNOP), diisobutyl phthalate (DIBP), di-n-hexyl phthalate (DNHP), diethyl phthalate (DEP), dicyclohexyl phthalate (DCHP), diethylene glycol dibenzoate esters (DEDB), epoxidized soybean oil (ESBO), citrates (citrates), citric acid esters, castor oil derivatives, epoxidized vegetable oils, succinates, tartaric acid, sorbitol, polyethylene glycol, starch, epoxidized soybean oil (ESBO), tributyl citrate (TBC), acetyl tributyl citrate (ATBC), triethyl citrate A (TEC-A), triclocarban (TCC), bis (2-ethylhexyl) maleate, bis (2-ethylhexyl) fumarate, DOML (linseed oil), DOP (castor oil base), DEHT (castor oil), GEFA, ELO, ESO, EVO, ELOV, ELOVAT, DOSA, DOA, DIDA, DES, DBS, PEG, lactic acid, oleic acid, PPG, PES, paraffin oil, naphthenic oil, esters or any combination thereof. Any other type of plasticizer may also be used.
[0039] In one embodiment, the coating includes at least one coupling agent. The coupling agent allows the coating to adhere to another surface, such as through an adhesive layer. The coupling agent is preferably added to the outer surface of the coating to optimally enhance the adhesion of the coating. In particular, the coupling agent includes at least one organosilane. An organosilane is a molecule having at least a single covalent bond between a silicon atom and a carbon atom within the molecule. In particular, the chemical structure of the organosilane is R (4-n) -Si-(R'X) n, wherein n=1 or 2; X is an organic functional group, such as vinyl, amino, methacryloyl, epoxy or any other functional group. When n>1, X can be a different functional group. An organofunctional group is the same as an organic functional group, i.e., a functional group containing at least one carbon atom. Organosilanes can form bridging molecules connected to the coating to improve the adhesion of the coating to another layer. Therefore, organosilanes are particularly suitable additives for coatings because these compounds can further increase the surface energy of the coating (especially the UV-resistant plasticizer coating), thereby improving its bonding properties. The increase in the surface energy of the coating increases its acceptability for bonding with other materials, thereby promoting better bonding of the coated panel to other materials through the adhesive layer through the formation of covalent bonds between the organosilane and the coating.
[0040] Preferably, the weight percentage of at least one coupling agent is in the range of 0.5-5.0 weight %, preferably 1.0-4.0 weight %, more preferably 2.0-3.0 weight %, and most preferably 2.3-2.7 weight %, based on the total weight of the coating. Experiments have found that these weight percentages can improve adhesion, improve the surface wettability of the coating in the uncured state, and increase the surface energy of the coating in the cured state, making the coating easier to bond with other materials.
[0041] The at least one coupling agent is selected from aminosilane, methacrylsilane, epoxysilane, vinylsilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, silane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropylphenyldimethylsiloxane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2,3-epoxypropyltrimethoxysilane, 2,3-epoxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltriphenoxysilane or any combination thereof.
[0042] The coating has a surface tension of at least 32 dyn / cm, preferably at least 34 dyn / cm, more preferably at least 36 dyn / cm, measured according to ASTM D7490-13 (2022). One disadvantage of the coating may be that its surface tension or surface energy is generally lower than the surface energy required for mounting the panels using an adhesive. If the surface tension is at least 32 dyn / cm, then the adhesion of the adhesive layer to the panels is sufficient. A surface tension above 32 dyn / cm, preferably above 34 dyn / cm, most preferably above 36 dyn / cm, is because it further enhances the adhesion ability of the coating.
[0043] Preferably, the panel comprises a top layer, preferably a decorative top layer, located on the top surface of the core layer. The decorative top layer provides an aesthetically pleasing panel. Optionally, a second coating may be provided on the top surface of the core layer, between the core layer and the top layer. Such a second coating may prevent the migration of plasticizer from the core layer to the top layer.
[0044] It is conceivable that the second coating is designed to receive a decorative print. Therefore, in another exemplary embodiment of the invention, on the top side of the panel core layer is at least one digital print layer with a digital print and on the back or bottom side of the core layer a coating for balancing is provided.
[0045] In another embodiment of the invention, the top surface of the panel and / or the decorative top layer at least partially comprises at least one viscoelastic coating and / or a thermosetting coating, at least a partial digitally printed layer and / or an excimer cured coating. It is also conceivable that the viscoelastic coating at least partially comprises a tactile texture and / or embossing formed thereon by chemical and / or mechanical methods. It is also conceivable that at least one embossed layer is substantially viscoelastic.
[0046] The decorative top layer may comprise at least one decorative layer and / or at least one protective layer. It is conceivable that at least one decorative layer is attached to the core layer. The decorative layer or decorative layer itself may also be a printed layer, in particular a digitally printed layer.
[0047] Preferably, the decorative top layer comprises a thermosetting protective layer or an at least partially ultraviolet (UV) cured protective layer. Additionally or alternatively, the cross-linked polymer may be a thermosetting resin. Thermosetting resins can be cured or hardened by undergoing a cross-linking reaction, thereby irreversibly forming a three-dimensional network. Thermosetting resins are generally liquid before curing and solid after curing. The curing process includes cross-linking, thereby curing the resin.
[0048] In a preferred embodiment, the decorative top layer comprises at least one decorative layer and / or at least one wear layer. For example, the wear layer may be a scratch resistant layer. The decorative top layer may comprise a wear layer or finishing layer, for example with a thermosetting varnish or paint, such as polyurethane, PUR, or melamine-based resin. In a preferred embodiment, the top layer comprises at least one substantially transparent wear layer or finishing layer. The wear layer may comprise one or more transparent layers of thermoplastic or thermosetting resin.
[0049] Non-limiting examples of thermoplastic or thermosetting resins that can be used include polyvinyl chloride (PVC), polystyrene (PS), polyethylene (PE), polyurethane (PU), acrylonitrile-butadiene-styrene (ABS), polypropylene (PP), polyethylene terephthalate (PET), phenolic resins and / or melamine or formaldehyde resins. The wear layer can also be applied in liquid or paste form made of thermosetting resins (e.g., including but not limited to phenolic and / or melamine or formaldehyde resins). The wear layer can include an inherently scratch-resistant thermosetting resin that impregnates a carrier layer (e.g., paper or lignocellulose), or can be essentially composed of such resin. Typically, the preferred thickness of the wear layer is between 0.1-2.0 mm, more preferably between 0.15-1.0 mm, and most preferably between 0.2-0.8 mm.
[0050] In one embodiment, the panel may include a decorative print provided by gravure printing or digital printing, a wood veneer, at least one cellulose layer, a ceramic and / or a stone veneer. For example, the decorative layer may include a plurality of impregnated layers that contain not only wood cellulose but also wood veneer, a thermoplastic layer, a stone veneer, a facing layer or similar materials, and / or combinations of the above materials.
[0051] The facing layer is preferably selected from wood facing, cork facing, bamboo facing, etc. Other materials such as ceramic tile or porcelain, real stone veneer, rubber veneer, decorative plastic or vinyl plastic, linoleum, and laminated decorative thermoplastic materials in the form of foil or film. Thermoplastic material can be PP, PET, PVC, etc. At least one thermoplastic can also be selected from polylactic acid (PLA), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), polyhydroxyurethane (PHU), cellulose acetate (CA), starch-based bioplastics, polyethylene terephthalate (PET), polyglycolic acid (PGA), polyhydroxyalkanoate-co-valerate (Polyhydroxyalkanoate-Co-Valerate, PHA-V), polybutylene adipate terephthalate (PBAT), etc.
[0052] The decorative layer, décor layer or decorative print can also form part of the core layer. In a beneficial embodiment of the panel, at least a portion of the upper surface of the core layer bears at least one decorative pattern or decorative image. For example, such a decorative image or pattern can be provided by printing, such as digital and / or inkjet printing. At least one decorative pattern can also be formed by embossing on the upper surface of the core layer or the panel. It is also contemplated that the décor layer or decorative layer is a separate layer, such as a high-pressure laminate (HPL), a veneer layer, a direct laminate paper layer and / or a tile.
[0053] The design of the decorative layer can be selected from a design database, which includes digitally processed designs, traditional patterns, picture or image files, custom digital artworks, random image patterns, abstract art, wood grain images, ceramic or concrete style images, or user-defined patterns. These patterns can be printed or reproduced using a laser printer, an inkjet printer or any other digital printing means including traditional printing methods. Various types of inks can also be used to meet the design requirements of the décor layer. Preferably, the ink used in the printing method has properties such as water resistance, lightfastness, acid-free, metallic, gloss, flashy, glittering or deep black, but is not limited thereto.
[0054] Preferably, the decorative layer is visually exposed through a substantially transparent coating. The décor layer can include patterns, where the patterns are printed by digital printing, inkjet printing, intaglio printing press, electronic line shaft (ELS) intaglio printing press, automatic plastic printing press, offset printing, flexographic printing or rotary printing press. The thickness of the decorative layer is preferably between 0.05 mm and 0.10 mm, such as 0.06 mm to 0.08 mm, such as 0.07 mm.
[0055] Preferably, according to ISO 23999 measurement, the coating has a shrinkage rate A, and according to ISO 23999 measurement, the protective layer has a shrinkage rate B, where B < A, and most preferably, where A ≈ 1.1·B. When tested at 80 °C according to ISO 23999, this achieves a balanced structure with the panel having a depression and bending of less than 1 mm.
[0056] In one embodiment, the core layer may comprise 10-40 wt % of an adhesive, 20-60 wt % of a mineral filler, and at least 4 wt %, preferably at least 6 wt %, and most preferably at least 8 wt % of a plasticizer, based on the total weight of the core layer. The relatively high mineral filler and plasticizer content, in combination, provides a panel that is wear resistant and flexible. The use of a coating is particularly advantageous for these types of panels due to the relatively high plasticizer content. The coating not only prevents the adhesive layer used to attach the panel to the surface from dissolving, but also prevents the core layer from becoming brittle due to the plasticizer molecules leaving the core layer.
[0057] The binder can be selected from polypropylene (PP), polyethylene terephthalate (PET), polyvinyl chloride (PVC), chlorinated polyvinyl chloride (CPVC), chlorinated polyethylene (CPE), polylactic acid (PLA), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), polyhydroxyurethane (PHU), cellulose acetate (CA), starch-based bioplastics, polyglycolic acid (PGA), polyhydroxyalkanoate-co-valerate (PHA-V), polybutylene terephthalate-adipate (PBAT), TPU, LDPE, LLDPE, HDPE, PS, HIPS, GPPS, PA, PETG, PPC, PC, ABS, PVDF, starch-based polymers, PHD, Bio-PE, LA, cellulose acetate, or any combination thereof.
[0058] Advantageously, the thickness of the coating may be in the range of 0.01-0.30 mm, preferably 0.05-0.25 mm, more preferably 0.10-0.20 mm, and most preferably 0.13-0.17 mm. A coating that is too thin requires a very high crosslinking density to effectively prevent the migration of plasticizer molecules. Such a high density reduces the flexibility of the coating and increases the brittleness of the panel, and is therefore undesirable in plasticized panels. Experiments have found that a coating with a thickness in the range of 0.13-0.17 mm is the best compromise in preventing the migration of plasticizer molecules while still having sufficient flexibility.
[0059] Preferably, the coating is formed by polymerization and crosslinking of at least one oligomer and at least one monomer, in particular by polymerization and crosslinking of acrylate oligomers and acrylate monomers. Acrylate oligomers provide flexibility, adhesion and wear resistance to the coating, while acrylate monomers help control the crosslinking density and improve the mechanical properties of the coating. When the coating is present between the core layer and the adhesive layer, the coating can also act as a barrier to prevent plasticizer molecules from diffusing to the adhesive layer and limit its fluidity, thereby preventing plasticizer migration. The coating itself prevents plasticizer migration and provides a sealing function for the lower surface of the core layer of the panel. Therefore, it can be understood as playing the role of a sealing layer and / or a plasticizer sealing layer.
[0060] The at least one oligomer, in particular the at least one acrylate oligomer, is selected from urethane acrylate oligomers, polyester-based urethane acrylate oligomers, aliphatic urethane acrylate oligomers, aromatic urethane acrylate oligomers, polyether-based urethane acrylate oligomers, water-based urethane acrylate oligomers, polyester acrylate oligomers, unsaturated polyester acrylates, polyester acrylates, tackified polyester acrylates, low molecular weight polyester acrylates, water-based polyester acrylates, epoxy acrylate oligomers, bisphenol A epoxy acrylates, aliphatic epoxy acrylates, cycloaliphatic epoxy acrylates, low viscosity epoxy acrylates, novolac epoxy acrylates, silicone acrylate oligomers, hydrophilic silicone acrylates, silicone acrylates, silicone-modified acrylates, low viscosity silicone acrylates and silicone-modified polyurethane acrylates.
[0061] According to the above, at least one monomer, especially at least one acrylate monomer can be selected from tetrahydrofurfuryl acrylate, pentaerythritol triacrylate, 2-hydroxyethyl acrylate (HEA), ethoxylated bisphenol A diacrylate (EBDA), trimethylolpropane triacrylate (TMPTA), isobornyl acrylate (IBOA) and cyclohexyl acrylate (CHA).
[0062] Preferably, the coating comprises a core-facing layer adjacent to the core layer and an opposite outer-facing layer, wherein: the core-facing layer comprises at least partially reactive carboxyl and / or amine functional groups, the core-facing layer is substantially inert to plasticizers, the outer-facing layer comprises at least one organosilane, and / or the outer-facing layer has a surface energy of at least 32 dyn / cm, preferably at least 34 dyn / cm, and more preferably at least 36 dyn / cm, as measured according to ASTM D7490-13(2022).
[0063] In a second aspect, the present invention relates to a composition for forming a coating, comprising:
[0064] 30-50% by weight of at least one acrylate oligomer,
[0065] 10-20 wt. % of at least one acrylate monomer, and
[0066] 1-5 wt. % of at least one photoinitiator.
[0067] With this composition a coating as described above can be formed. The photoinitiator is preferably capable of initiating an ultraviolet (UV) curing process of the composition. Advantageously, the composition can be a liquid composition so that it can be easily applied to the core of the panel before curing. This composition can be applied to the panel and the resulting coating has all the advantages as described above.
[0068] Preferably, at least one acrylate oligomer is selected from urethane acrylate oligomers, polyester-based urethane acrylate oligomers, aliphatic urethane acrylate oligomers, aromatic urethane acrylate oligomers, polyether-based urethane acrylate oligomers, water-based urethane acrylate oligomers, polyester acrylate oligomers, unsaturated polyester acrylates, polyester acrylates, tackified polyester acrylates, low molecular weight polyester acrylates, water-based polyester acrylates, epoxy acrylate oligomers, bisphenol A epoxy acrylates, aliphatic epoxy acrylates, cycloaliphatic epoxy acrylates, low viscosity epoxy acrylates, novolac epoxy acrylates, silicone acrylate oligomers, hydrophilic silicone acrylates, silicone acrylates, silicone-modified acrylates, low viscosity silicone acrylates, silicone-modified polyurethane acrylates, or any combination thereof.
[0069] The at least one acrylate monomer may be selected from tetrahydrofurfuryl acrylate, pentaerythritol triacrylate, 2-hydroxyethyl acrylate (HEA), ethoxylated bisphenol A diacrylate (EBDA), trimethylolpropane triacrylate (TMPTA), isobornyl acrylate (IBOA), cyclohexyl acrylate (CHA), or any combination thereof.
[0070] At least one photoinitiator can be selected from α-hydroxy ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), 1-hydroxycyclohexyl phenyl ketone (HCPK), dibenzophenone, dibenzophenone (BP), 4,4'-bis(dimethylamino)benzophenone, phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (TPO), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, acylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO-L), 2,4,6-trimethylbenzoylphenylphosphine oxide (TPO-P), iodonium salt, diphenyliodonium hexafluorophosphate (DPI-HFP) and (4-methylphenyl)-phenyliodonium hexafluoroantimonate (MPI-HFA), or any combination thereof.
[0071] The composition may comprise at least one organosilane. In particular, the weight percentage of the at least one organosilane is between 0.5 and 5 weight %, based on the total weight of the composition. This provides the advantages disclosed above.
[0072] According to the above, at least one organosilane may be selected from aminosilane, methacrylsilane, epoxysilane, vinylsilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, dimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropylphenyldimethylsiloxane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2,3-epoxypropyltrimethoxysilane, 2,3-epoxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltriphenoxysilane or any combination thereof.
[0073] In a third aspect, the invention relates to a method of manufacturing a panel as disclosed above, comprising:
[0074] providing a core layer comprising at least one mineral filler and at least one polymer binder,
[0075] Optionally, providing at least a portion of the top surface of the core layer with a decorative top layer,
[0076] applying the composition disclosed above to at least a portion of the bottom surface of the core layer, and
[0077] The composition is at least partially crosslinked to obtain a coating.
[0078] The core layer may be provided by mixing together a mineral filler, a thermoplastic, a plasticizer and optional additives to form a thermoplastic melt. The core layer may be obtained by extruding the thermoplastic melt. The core layer may comprise at least one plasticizer, such as the plasticizers described above for the panel.
[0079] Preferably, the composition is 10-90 g / m 2 The weight range of the composition is applied to at least a portion of the bottom surface of the core layer. Advantageously, the composition can be used in an uncured state. Such a weight per unit area of the composition can effectively prevent the plasticizer molecules from migrating through the coating by curing the composition.
[0080] Preferably, curing the composition comprises curing the composition with ultraviolet light, at least one excimer, pressure, infrared light, electron beam curing (EBC), temperature, or any combination thereof. UV curing is an effective curing method that can be simply achieved with ultraviolet light. The wavelength of ultraviolet light is shorter than visible light, but longer than X-rays. The wavelength of ultraviolet light is generally between 100 and 400 nm.
[0081] According to the present invention, the panel may further include at least one top layer, preferably a decorative top layer. Such a decorative top layer may be, for example, a high pressure laminate (HPL), a plurality of impregnated layers comprising lignocellulose, a wood veneer, a thermoplastic layer comprising at least one decorative layer and an optional protective top layer, a stone veneer, etc., and / or a combination of said decorative layers. The decorative top layer may also include at least one cellulose base layer and a cured resin, wherein the cellulose base layer is preferably paper or kraft paper. The cellulose-based material layer may also be a facing layer adhered to the upper surface of the core layer. The facing layer is preferably selected from wood veneer, cork veneer, bamboo veneer, etc. According to the present invention, other decorative top layers that may be considered include ceramic or porcelain, real stone veneer, rubber veneer, decorative plastic or vinyl plastic, linoleum, and decorative thermoplastic film or foil, which may be laminated with a wear layer and a coating. Examples of thermoplastics may be PP, PET, PVC, etc. An optional primer may also be provided on the top surface of the core and the desired visual effect may be printed in a direct printing process. The decorative layer may further be coated with a thermosetting varnish or paint, such as polyurethane (PUR) or melamine resin. The panel, especially the top layer, may optionally comprise at least one gloss control layer. The panel, especially the top layer, may also comprise at least one, preferably a plurality of acrylic coatings.
[0082] It is further conceivable that a coating is provided on the bottom side of the panel, wherein the coating is a viscoelastic coating and / or a thermosetting coating and / or an excimer-cured coating.
[0083] It is conceivable that the wear-resistant particles are dispersed, at least partially enclosed or embedded, preferably completely enclosed or embedded, by at least one coating. It is also conceivable that the wear-resistant particles are dispersed, at least partially enclosed or embedded, preferably completely enclosed and embedded in at least one coating and / or wear-resistant layer, so that the wear-resistant particles are enclosed by at least one coating, and / or by at least one wear-resistant layer, preferably, by at least two wear-resistant layers, and / or by at least one top layer.
[0084] It is likewise conceivable that the wear-resistant particles are selected from the group consisting of aluminum oxide, corundum, silicon carbide, titanium dioxide, titanium oxide and / or diamond particles or diamond powder.
[0085] In further embodiments, at least one coating may further comprise an antimicrobial, antiviral, antibacterial, and / or antifungal agent.
[0086] In a preferred embodiment, the panel comprises at least one sound absorbing pad adhered to the back of the core layer. The padding layer may also be referred to as a buffer layer or a damping layer. The padding layer is typically made of a polymeric material, such as, but not limited to, a low density foam layer of ethylene vinyl acetate (EVA), radiation cross-linked polyethylene (IXPE), expanded polypropylene (XPP) and / or expanded polystyrene (XPS). However, it is also conceivable that the padding layer comprises non-woven fibers, such as natural fibers, such as hemp or cork, and / or recycled / recyclable materials, such as PET, felt, recycled carpet, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] The invention will now be explained by means of non-limiting exemplary embodiments based on the following figures. In this:
[0088] Figure 1 is a perspective view of a prior art panel containing plasticizer molecules;
[0089] Figure 2 is a cross-sectional view of a panel according to the present invention;
[0090] Figure 3 is a cross-sectional view of another panel according to the present invention;
[0091] Figure 4 is a cross-sectional view of another panel according to the present invention;
[0092] Figure 5 is a cross-sectional view of another panel having an acoustic absorbing liner according to the present invention;
[0093] Figure 6 is a cross-sectional view of another panel according to the present invention, comprising embossing on a top protective layer and a multi-layer coating;
[0094] Figure 7 is a cross-sectional view of another panel according to the invention comprising an embossed layer;
[0095] Figure 8 is a cross-sectional view of another panel according to the present invention, the panel comprising a pre-attached acoustic substrate;
[0096] Fig. 9 is a cross-sectional view of a wall panel according to the present invention;
[0097] Fig.10 is a schematic diagram of cross-linking in the coating;
[0098] Fig.11a , 11b 11c and 11c show the crosslinking in the coating at different densities (i.e., 50%, 60%, and 70%). Fig.11d It is a reference picture;
[0099] Fig.12a is a schematic diagram of the relationship between cross-link density and void diameter; Figure 12b is a reference schematic;
[0100] Fig.13 is a schematic diagram of an alternative embodiment of a top layer according to the present invention;
[0101] Fig.14 is a schematic diagram of an alternative embodiment of a top layer having a digital printing layer according to the present invention;
[0102] Fig.15 is a schematic diagram of an alternative embodiment according to the present invention further comprising an embossed top layer;
[0103] Fig.16 is a schematic diagram of an alternative embodiment of a top layer without a wear-resistant layer according to the present invention;
[0104] Fig.17 is a schematic diagram of an alternative embodiment of a top layer further comprising a gloss control layer according to the present invention;
[0105] Fig.18 is a schematic diagram of an alternative embodiment of a top layer further comprising at least one acrylic layer according to the present invention;
[0106] Fig.19 is a schematic diagram of an alternative embodiment of a top layer, wherein embossing is applied to at least a portion of at least one acrylic layer according to the present invention;
[0107] Fig. 20 is a schematic diagram of an alternative embodiment of a top layer further comprising a gloss control layer, wherein embossing is applied to at least a portion of at least one acrylic layer according to the present invention;
[0108] Fig.21 is a schematic diagram of another aspect of the present invention;
[0109] Fig. 22 is a schematic diagram of another aspect of the present invention;
[0110] Fig.23 is a schematic diagram of another aspect of the present invention.
[0111] In these figures, the same reference numerals indicate similar or equivalent technical features. DETAILED DESCRIPTION
[0112] Figure 1A perspective view of a prior art panel 101 mounted on a substrate 200 is shown. The panel 101 comprises a core layer 102 and a top coating 103. The panel 101 is curved or concave due to the curing of the top coating 103 during the manufacturing process of the panel 101. The side edges of the panel including the mutually matching connecting means 104, 105 are at a relatively large distance from the substrate 200 compared to the distance of the center 106 of the panel 101 from the substrate 200.
[0113] The panel 101 is adhered to the substrate 200 by means of the adhesive layer 107. Plasticizer molecules 108 have migrated from the core layer 102 of the panel 101 into the adhesive layer 107. The adhesive layer 107 is thereby liquefied.
[0114] Figure 2 A cross section of a panel 101 according to the present invention is shown, wherein the panel 101 is mounted on a substrate 200, such as a floor surface. The panel 101 comprises connecting means 104, 105 that match each other. The panel comprises a coating 110 located on the bottom surface of a core layer 102. Plasticizer molecules 108 are distributed on the core layer 102. Since the coating 110 is cured, it has shrunk during the manufacturing process of the panel. Therefore, the coating 110 balances the panel 101 so that the panel 101 is flat. Since the lower bottom surface 111 of the coating 110 and the substrate 200 are aligned, the adhesive layer 107 has a uniform thickness. Due to the uniform thickness of the adhesive layer, the adhesion between the panel 101 and the substrate 200 is improved.
[0115] During the manufacturing process of the panel 101, the curing of the coating 110 not only shrinks the coating 110, but also crosslinks the oligomers and monomers in the coating to form a polymer network. The polymer network contains relatively small diameter voids, which prevent the plasticizer molecules 108 from migrating through the coating 110 into the adhesive layer 107. Therefore, the adhesive layer 107 does not liquefy.
[0116] See also Figure 3 , shows a panel 101 mounted on a substrate 200. The panel 101 comprises complementary coupling means 104, 105. The panel 101 is different from Figure 2 A panel in which the additional coating 110c is located between the top layer 103 and the core layer 102 comprising plasticizer molecules 108. Figure 3The top layer 103 of the panel 101 is a decorative top layer including a printed pattern. The coating layer 110c directly below the top layer 103 prevents the plasticizer molecules 108 from migrating from the core layer 102 into the printed pattern. In this way, the coating layer 110c directly below the top layer 103 prevents the ink from dissolving in the printed pattern. Therefore, the printed pattern can be maintained for a long time. In addition, due to the presence of the organosilane, the coating layer 110 between the core layer 102 and the adhesive layer 107 can enhance the adhesion and compatibility with the adhesive and improve the balance during temperature fluctuations.
[0117] Figure 4 An embodiment of a panel 101 of the invention is shown, wherein the panel 101 is mounted on a substrate 200 and comprises a top layer 103, the top layer 103 comprising at least one visual design and at least one protective layer, the top layer 103 having a first shrinkage, at least one coating 110a having at least one carboxyl functional group capable of reacting with at least one plasticizer, and at least one coating 110b having at least one organosilane, thereby enabling a strong bond with an adhesive layer 107, wherein the coatings 110a and 110b have a second shrinkage greater than the first shrinkage of the top layer 103, preferably about 10% greater than the first shrinkage of the top layer, thereby balancing the structure. Thus, the panel 101 has a cupping rate of less than 1 mm, preferably less than 0.5 mm, when measured according to ISO 23999. The panel 101 in the manner shown has no connecting means.
[0118] like Figure 5 As further illustrated in the panel 101 mounted on a substrate 200, a top layer 103 comprising plasticizer molecules 108 is provided on the top surface of a core layer 102. The panel 101 comprises an acoustically absorbing substrate 202 attached to the back of a coating 110, which is adhered to the core layer 102 by an adhesive layer 107. The panel 101 comprises mutually matching connecting means 104, 105.
[0119] like Figure 6 As shown in the panel 101, the top layer 103 is a top protective layer 103, including a top sealing layer 1031, a decorative printing layer 1032 and a top protective layer 1033 with embossing. Figure 6 The illustrated panel 101 includes a plurality of coatings 110, 111 contained in the panel 101 such that the first bottom coating 110 and the second bottom coating 111 represent a plurality of coatings disposed on a bottom surface of the core layer 102. The panel 101 is mounted on a substrate 200, and the core layer 102 includes plasticizer molecules 108.
[0120] like Figure 7The panel 101 shown has a tactile embossed or textured layer 1034. The mechanically or chemically applied textured layer 1034 is present between a top coating 1035 and at least one protective layer 1033. The entirety of the top layer 103 structure, including the top sealing layer 1031, the decorative print layer 1032, the protective layer 1033, the embossed layer 1034 and the top coating 1035, in combination has a first shrinkage; and the entirety of at least one bottom coating 110, 111 or sealing layer combination has a second shrinkage, such as the first coating 110 and the second coating 111, which is greater than the first shrinkage of the top layer 103 structure, preferably about 10% greater than the first shrinkage of the top layer, thereby balancing the structure. Therefore, the panel 101 has a cupping rate of less than 1 mm, preferably less than 0.5 mm when measured according to ISO 23999. It is contemplated that at least one coating layer 110 includes at least one carboxyl functional group capable of reacting with at least one plasticizer, and / or its average cross-linked void diameter is smaller than the average diameter of the plasticizer, and / or at least one second coating layer 111 includes at least one organosilane, thereby being able to firmly bond with the adhesive layer 107. As shown, the panel 101 is mounted on the substrate 200, and the core layer 102 includes plasticizer molecules 108.
[0121] Figure 8 The panel 101 in the embodiment includes a pre-attached acoustic substrate 203, which is adhered to the panel 101 by an adhesive layer 107. The first bottom coating 110 and the second bottom coating 111 ensure the integrity of the adhesive and the stability and flatness of the panel. As shown, the panel 101 is installed on the substrate 200, and the core layer 102 includes plasticizer molecules 108. The top layer 103 includes a top sealing layer 1031, a decorative printing layer 1032, a protective layer 1033 and an embossed layer 1034.
[0122] Fig. 9 Another exemplary embodiment of a panel 101 according to the present invention is shown, the panel 101 being constructed as a wall panel and attached to a wall substrate 200. Tongue and groove connection means 104 and 105 for a locking mechanism of the wall panel 101 are provided here. The core layer 102 includes plasticizer molecules 108 dispersed on the core layer 102. As shown, the panel 101 includes a plurality of coating layers 110, 111, which are included in the panel 101, such that the first bottom coating layer 110 and the second bottom coating layer 111 represent a plurality of coating layers disposed on the bottom surface of the core layer 102. The top layer 103 includes a top sealing layer 1031, a decorative print layer 1032, and a protective layer 1033.
[0123] Fig.10 A portion of a panel 101 is shown, wherein a portion of the coating 110 (represented by a square) is enlarged and shown schematically. Fig.10The enlarged square in the figure shows the three-dimensional network defined by the polymer backbone 1101 and the cross-links 1102. Fig.10 The cross-linked nature of the polymer coating or coating 110 is further shown. The void diameter Vdia 1103 (the diameter of the dashed circle) is a measure of the average size of the voids / spaces within the three-dimensional network of the cross-linked polymer. The panel 101 also includes a core layer 102 containing plasticizer molecules 108 and a decorative top layer 103. The panel may optionally be provided with a connecting device 104.
[0124] Fig.11a , 11b and 11c show schematic diagrams of a three-dimensional network defined by polymer backbones 1101 and cross-links 1102 of different cross-linking densities. Fig.11a , 11b The crosslinking density of the three-dimensional network in 1102 and 11c is 50%, 60% and 70%, respectively. The number and interconnectivity of the crosslinking bonds 1102 increase with the increase of the crosslinking density. Figure 2-9 , the increase in crosslink density reduces the void diameter in the polymer coating 110, which is smaller than the gyration diameter of the plasticizer molecules 108. Therefore, the adhesive layer 107 does not liquefy. Then, the coating 110 acts as a mechanical barrier to inhibit the migration of the plasticizer molecules 108 from the core layer 102 to the adhesive layer 107. Fig.11d Shows Figures 11a-11c Reference graph of cross-link density shown, which shows the effect of increasing cross-link density.
[0125] Fig.12a The relationship between crosslink density and void diameter is shown, so the crosslink density is inversely proportional to the void diameter of the coating polymer network. The figure shows that the sharp decrease in void diameter is due to the increase in the crosslink density of the coating. In a densely crosslinked network, the possibility of void formation is less, and the void diameter is generally smaller. As the crosslink density decreases, the connectivity of the network decreases, resulting in the formation of larger voids.
[0126] In addition, the molecular weight of the polymer, the degree of crosslinking, and the presence of plasticizers or other additives can affect the size and distribution of the voids. The network topology, such as the crosslinking arrangement, can also have a significant impact on the void structure.
[0127] Figure 12b is a reference graph showing the histogram of nanovoid volume for poly(dicyclopentadiene) (pDCPD) and poly(5-ethylidene-2-norbornene) (pENB) under uniaxial extension at depth in the glassy state (150 K) at engineering strains of 0% (solid symbols) and 35% (open symbols). The inset shows the volume percentage of nanovoids, i.e., the percentage of the volume of the simulation box occupied by nanovoids.
[0128] Fig.13 A schematic exploded view of another possible embodiment of a panel 101 according to the invention is shown. It is conceivable that the top layer 103 of the panel comprises at least one top coating 1031, at least one tactile or texture layer 1033 and (optionally) at least one wear layer 1034. The top layer 103 is at least partially arranged on the top surface of the core layer 102, and the coating 110 is arranged on the bottom surface of the core layer 102. The thickness of the at least one wear layer is at least 0.2 mm, most preferably up to 0.5 mm. It is conceivable that at least two wear layers are provided, wherein it is conceivable that a layer with a weight of 20-50 g / m is provided between the two wear layers. 2 , preferably 30-35g / m 2 About wear-resistant particles.
[0129] Fig.14 A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown, in particular a top layer 103 of the panel. The panel comprises a top layer 103 comprising a coating 1031, at least one textured or embossed layer 1035, a gloss control layer 1036, an acrylic coating 1037 comprising 5-15% by weight of wear resistant particles, a decorative print layer 1032 and a primer layer 1038. The at least one acrylic coating 1037 may also comprise dispersed wear resistant particles. The embossed layer 1035 may be a viscoelastic coating. The decorative print layer 1032 may optionally be a digital print layer. The top layer 103 is at least partially disposed on the top surface of a core layer 102, and an optional coating 110 is disposed on the bottom surface of the core layer 102.
[0130] Fig.15 A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown, in particular a possible embodiment of a top layer 103 according to the invention. The panel 101 comprises a top layer 103, which optionally comprises a top coating 1031, at least one embossing layer 1035, a gloss control layer 1036, at least one wear layer 1034, wherein it is conceivable to provide at least two wear layers and / or to provide a layer with a weight of 20-50 g / m2 between at least two wear layers. 2 , preferably 30-35g / m 2 The top layer 103 is provided with a ceramic bead loading, a decorative print layer 1032 and / or a primer layer 1038. The embossing is provided at least partially on the top layer 103 by mechanical, chemical or abrasive means, wherein the top coating 1031 covers at least part of the embossed layer 1035. The top layer 103 is at least partially disposed on the top surface of the core layer 102, and the optional coating 110 is disposed on the bottom surface of the core layer 102.
[0131] Fig.16A schematic exploded view of another alternative embodiment of a panel 101 according to the invention is shown, in particular a top layer 103 of the panel. The panel comprises a top layer 103, which optionally comprises a top coating 1031, at least one embossing layer 1034, a gloss control layer 1036, a decorative print layer 1032 and / or a primer layer 1038. The embossing is at least partially arranged on the top layer 103, in particular extending vertically in the embossing layer 1034, wherein the top coating 1031 covers at least a part of the embossing layer 1034. The top layer 103 is at least partially arranged on the top side of the core layer 102, and the optional coating 110 is arranged on the bottom side of the core layer 102.
[0132] Fig.17 A schematic exploded view of an alternative embodiment of a panel 101 according to the present invention is shown, in particular a top layer 103 of the panel 101. The panel 101 comprises a top layer 103, which preferably comprises a top coating 1031, at least one embossing layer 1035, a gloss control layer 1036, a wear layer 1034, a decorative print layer 1032 and / or a primer layer 1038. The thickness of at least one wear layer 1034 is at least 0.2 mm, most preferably at most .5 mm. It is conceivable that at least a portion of at least one embossing layer 1035 and / or gloss control layer 1036 is covered by the top coating 1031. It is further envisaged that the embossing layer 1035 is a viscoelastic coating and the decorative print layer 1032 is a digital print layer. The top layer 103 is at least partially disposed on the top surface of the core layer 102, and the optional coating 110 is disposed on the bottom surface of the core layer 102.
[0133] Fig.18 A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown, in particular a top layer 103 of the panel 101. The panel 101 comprises a top coating 103, which preferably comprises at least one acrylic coating 1037, a decorative print layer 1032 and / or at least one wear layer 1034. The thickness of the at least one wear layer is at least 0.2 mm, most preferably at most 0.5 mm. It is conceivable that the embossing is applied to at least a portion of the acrylic coating 1037, at least a portion of the decorative print layer 1032 and / or at least a portion of the core layer 102. The core layer 102 comprises plasticizer molecules 108. The top layer 103 is at least partially disposed on the top surface of the core layer 102, and the optional coating 110 is disposed on the bottom surface of the core layer 102. It is further envisaged that at least one acrylic coating 1037 comprises wear resistant particles in the range of 1% to 30%, preferably in the range of 1% to 10%.
[0134] Fig.19A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown, in particular a top layer 103 of the panel 101. The panel 101 comprises a top layer 103, which preferably comprises a top coating 1031, at least one embossing layer 1035, a plurality of acrylic coatings 1037 and / or a wear layer 1034. The thickness of the at least one wear layer 1034 is at least 0.2 mm, most preferably at most 0.5 mm. It is conceivable that the embossing is applied to at least a portion of the embossing layer 1035, the at least one acrylic coating 1037 and / or at least a portion of the wear layer 1034. It is further conceivable that at least one embossing layer 1035, the at least one acrylic coating 1037 and / or at least a portion of the wear layer 1034 is covered by the top coating 1031. It is also conceivable that the at least one acrylic coating 1037 contains wear resistant particles in the range of 1% to 30%, preferably in the range of 1% to 10%. The top layer 103 is at least partially disposed on the top surface of the core layer 102 , and the optional coating layer 110 is disposed on the bottom surface of the core layer 102 .
[0135] Fig. 20 A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown, in particular a top layer 103 of the panel 101. The panel 101 comprises a top layer 103, which preferably comprises a top coating 1031, at least one embossed layer 1035, a plurality of acrylic coatings 1037, a gloss control layer 1036 and / or a wear layer 1034. The thickness of the at least one wear layer 1034 is at least 0.2 mm, most preferably at most 0.5 mm. It is conceivable that the embossing is applied to at least a portion of the embossed layer 1035, and / or at least a portion of the acrylic coating 1037. It is further conceivable that at least one embossed layer 1035, at least one acrylic coating 1037 and / or at least a portion of the wear layer 1034 is covered by the top coating 1031. It is also conceivable that at least one acrylic coating 1037 contains wear resistant particles in the range of 1% to 30%, preferably in the range of 1% to 10%. The top layer 103 is at least partially disposed on the top surface of the core layer 102 , and the optional coating layer 110 is disposed on the bottom surface of the core layer 102 .
[0136] Fig.21Another schematic exploded view of an alternative embodiment of a panel 101 according to the present invention is shown. The panel 101 includes a top layer 103, and also includes a thin top layer 1031, at least one embossed layer 1050, at least one first wear-resistant layer 1034a, and / or at least one second wear-resistant layer 1034b. At least one scattering layer 1060, such as an aluminum oxide scattering layer, can be arranged below the at least one first wear-resistant layer 1034a and / or above the at least one second wear-resistant layer 1034b. The wear-resistant particles can be dispersed, at least partially enclosed or embedded, preferably completely enclosed or embedded by the at least one first wear-resistant layer 1034a and the at least one second wear-resistant layer 1034b after adhering to each other. The top layer 103 is at least partially arranged on the top surface of the core layer 102, and the optional coating 110 is arranged on the bottom surface of the core layer 102.
[0137] Fig. 22 A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown. The panel 101 comprises a top layer 103, a core layer 102 and at least one coating 110. The top layer 103 optionally comprises a top coating 1031, at least one wear layer 1034 and a decorative print layer 1032. It is conceivable that the thickness of the at least one wear layer 1034 is between 0.2 and 0.5 mm. It is further conceivable that the decorative print layer 1032 is a digital print layer and / or an impregnated paper layer. If an impregnated paper layer is used, a cover layer 1039 is added between the impregnated paper and the core layer 102, preferably adjacent to the impregnated paper.
[0138] Fig.23 A schematic exploded view of an alternative embodiment of a panel 101 according to the invention is shown. The panel 101 comprises a top coating 103, a core layer 102 and at least one coating 110. The top layer 103 comprises a top coating 1031, a digital print layer 1032 and a primer layer 1308.
[0139] It is obvious that the invention is not limited to the working examples shown and described herein, but that it is susceptible of numerous modifications within the scope of the appended claims, which will be obvious to a person skilled in the art.
[0140] The verb "comprise" and its conjugations used in this patent publication means not only "include", but also "comprising", "consisting essentially of", "formed of" and their conjugations.
Claims
1. A panel, in particular a floor panel or a wall panel, comprising: at least one core layer comprising at least one mineral filler, at least one polymer binder and at least one plasticizer; and at least one coating located on the bottom surface of the at least one core layer; wherein the at least one coating comprises at least partially crosslinked polymer that is impermeable to at least one plasticizer.
2. The panel according to claim 1, wherein The at least partially crosslinked polymer comprises a crosslinked polymer network; the at least partially crosslinked polymer has a crosslink density of at least 50%, more preferably at least 60%, most preferably at least 65%.
3. The panel according to claim 2, wherein The crosslinked polymer network comprises a plurality of voids, and wherein the average void diameter is less than or equal to the radius of gyration of the at least one plasticizer.
4. The panel according to any one of claims 1 to 3, wherein: The at least one plasticizer has a plasticizer migration rate through the at least one coating layer of less than 0.01 mg / cm2 as measured according to ISO 177:2016 2 .
5. The panel according to any one of claims 1 to 4, wherein: The at least partially crosslinked polymer is inert to the at least one plasticizer.
6. The panel according to any one of claims 1 to 5, wherein: The at least one plasticizer is an external plasticizer.
7. The panel according to any one of claims 1 to 6, wherein: Based on the total weight of the at least one coating, the at least one coating contains at least one coupling agent in the range of 0.5 - 5.0% by weight; wherein the at least one coupling agent comprises at least one organosilane.
8. The panel according to any one of claims 1 to 7, wherein: Measured according to ASTM D7490 - 13(2022), the at least one coating has a surface tension of at least 32 dyn / cm, preferably at least 34 dyn / cm, more preferably at least 36 dyn / cm.
9. The panel according to any one of claims 1 - 8, comprising a decorative top layer located on the top surface of the at least one core layer; the decorative top layer comprises a thermosetting protective layer or at least partially UV - cured protective layer.
10. The panel according to claim 9, wherein When measured according to ISO 23999, the at least one coating has a shrinkage rate A, and when measured according to ISO 23999, the protective layer and / or the decorative top layer has a shrinkage rate B, wherein, B < A, most preferably A ≈ 1.1·B.
11. The panel according to any one of claims 1 to 10, wherein: Comprising a decorative top layer located on the top surface of the at least one core layer; the core layer comprises a decorative print, a wood veneer, at least one layer of cellulose, a ceramic and / or a stone veneer provided by gravure printing or digital printing.
12. The panel according to any one of claims 1 to 11, wherein Based on the total weight of the at least one core layer, the at least one core layer contains 10 - 40% by weight of the binder, 20 - 60% by weight of the at least one mineral filler and at least 4% by weight, preferably at least 6% by weight, most preferably at least 8% by weight of the at least one plasticizer.
13. The panel according to any one of claims 1 to 12, wherein: The at least one binder is selected from polypropylene (PP), polyethylene terephthalate (PET), polyvinyl chloride (PVC), chlorinated polyvinyl chloride (CPVC), chlorinated polyethylene (CPE), polylactic acid (PLA), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), polyhydroxyurethane (PHU), cellulose acetate (CA), starch-based bioplastics, polyglycolic acid (PGA), polyhydroxyalkanoate-co-valerate (PHA-V), polybutylene adipate terephthalate (PBAT), TPU, LDPE, LLDPE, HDPE, PS, HIPS, GPPS, PA, PETG, PPC, PC, ABS, PVDF, starch-based polymers, PHD, Bio-PE, LA, cellulose acetate, or any combination thereof.
14. A panel according to any one of claims 1 to 13, wherein: The at least one coating layer is formed by polymerizing and crosslinking at least one oligomer and at least one monomer, in particular, by polymerizing and crosslinking acrylate oligomers and acrylate monomers.
15. The panel according to any one of claims 1 to 14, wherein The at least one coating layer comprises a core-facing layer adjacent to the core layer and an opposing outer-facing layer, wherein: The core-facing layer comprises at least part of reactive carboxyl and / or amine functional groups, The core-facing layer is substantially inert to the plasticizer, The outer-facing layer comprises at least one organosilane, and / or The outer-facing layer has a surface energy of at least 32 dyn / cm, preferably at least 34 dyn / cm, more preferably at least 36 dyn / cm, measured according to ASTM D7490-13 (2022).
16. A composition for forming at least one coating, comprising: 30-50% by weight of at least one acrylate oligomer, 10-20 wt. % of at least one acrylate monomer, and 1-5 wt. % of at least one photoinitiator.
17. The composition according to claim 16, wherein The at least one acrylate oligomer is selected from urethane acrylate oligomers, polyester-based urethane acrylate oligomers, aliphatic urethane acrylate oligomers, aromatic urethane acrylate oligomers, polyether-based urethane acrylate oligomers, water-based urethane acrylate oligomers, polyester acrylate oligomers, unsaturated polyester acrylates, polyester acrylates, tackified polyester acrylates, low molecular weight polyester acrylates, water-based polyester acrylates, epoxy acrylate oligomers, bisphenol A epoxy acrylates, aliphatic epoxy acrylates, alicyclic epoxy acrylates, low viscosity epoxy acrylates, novolac epoxy acrylates, silicone acrylate oligomers, hydrophilic silicone acrylates, silicone acrylates, silicone-modified acrylates, low viscosity silicone acrylates, silicone-modified polyurethane acrylates, or any combination thereof.
18. The composition according to claim 16 or 17, wherein The at least one acrylate monomer is selected from tetrahydrofurfuryl acrylate, pentaerythritol triacrylate, 2-hydroxyethyl acrylate (HEA), ethoxylated bisphenol A diacrylate (EBDA), trimethylolpropane triacrylate (TMPTA), isobornyl acrylate (IBOA), cyclohexyl acrylate (CHA), or any combination thereof.
19. The composition according to any one of claims 16 to 18, wherein The at least one photoinitiator is selected from α-hydroxy ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), 1-hydroxycyclohexyl phenyl ketone (HCPK), benzophenone, benzophenone (BP), 4,4'-bis(dimethylamino)benzophenone, phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (TPO), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, acylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO-L), 2,4,6-trimethylbenzoylphenylphosphine oxide (TPO-P), iodonium salt, diphenyliodonium hexafluorophosphate (DPI-HFP) and (4-methylphenyl)-phenyliodonium hexafluoroantimonate (MPI-HFA), or any combination thereof.
20. The composition according to any one of claims 16 to 19, comprising at least one organosilane; the weight percentage of the at least one organosilane is in the range of 0.5 to 5 weight % based on the total weight of the composition; and wherein, The at least one organosilane is selected from aminosilane, methacrylsilane, epoxysilane, vinylsilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, silane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropylphenyldimethylsiloxane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2,3-epoxypropyltrimethoxysilane, 2,3-epoxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltriphenoxysilane, or any combination thereof.
21. Method of manufacturing a panel according to any one of claims 1 to 15, comprising: providing a core layer comprising at least one mineral filler and at least one polymer binder, Optionally, providing at least a portion of the top surface of the core layer with a decorative top layer, applying a composition according to any one of claims 16 to 20 to at least a portion of the bottom surface of the core layer, and The composition is at least partially crosslinked to obtain an at least partially crosslinked coating.
22. The method according to claim 21, wherein: The composition is mixed at 10-90 g / m 2 The mass range is coated to at least a portion of the bottom surface of the core layer.